Influence of Welding Variables on the Microstructural and Tensile Properties of 304L Austenitic Stainless Steel Heat Affected Zone - Oyetunji, A. (Kathmandu University Journal of Science, Engineering and Technology, 2015)
This work investigates the effects of welding speeds and power inputs at different ranges on the Heat Affected Zone (HAZ), microstructural characteristics, and tensile behavior of type 304L austenitic stainless steel. Chemical analysis of the as-received 304L austenitic stainless steel was done to determine its chemical composition. Thereafter, the as-received 304L austenitic stainless steel plate was cut with a hacksaw into samples of dimensions 70 mm length, 45 mm breadth, and 8 mm thickness. Thirty samples were produced in all, with ten samples each assigned to groups A, B, and C respectively. The grouped samples were further cut into two equal halves with a hacksaw and welded using Gas Metal Arc Welding (GTAW) process and 304L electrode to produce butt joint HAZ square geometry samples. The obtained HAZ samples and as-received sample were machined to standard tensile test specimens, and tensile tests were made using standard approaches. The HAZ and as-received specimens were prepared for microscopy studies and etched in a solution of 1 ml HCl + 3 ml HNO3 + 1 ml glycerol, and the microstructures were examined using a metallurgical microscope at a magnification of 400x. Results obtained show that the microstructures are composed mainly of a mixture of austenite and ferrite phases. Also, variations in volume fraction and grain size of the phases were observed at the different welding speeds and power inputs. In addition, chromium carbide formation and precipitation due to sensitization were seen at the grain boundaries. Also, optimum ultimate tensile strength (UTS) and yield strength (YS) were obtained for HAZ sample at moderate (4.5 mm/s) welding speed, and optimum % elongation at slow welding speed. Optimum UTS and YS were obtained for HAZ sample at a power input of 9.2 KW, and optimum % elongation at 12.00 KW. Generally, when compared with the as-received sample, a remarkable influence of the welding variables on the tensile characteristics of the material’s HAZ was noticed.